Clinical and ultrasonography evaluation of thyroid tumor screening in symptomatic patient of Bajulmati primary care center, Banyuwangi, East Java, Indonesia - Setiawati, Rosy; Wulanhandarini, Tri; Hayati, Fierly; Erawati, Dyah; Jaya, Merlin Guntur; Thoriq, Andi Ahmad; Wijaya, Triana Mediyawati; Ismiyati, Galih Nur; Kusumaningrum, Dyan Wahyu; Koesmarsono, Belinda; Basja, Agnes Triana; Nugroho, M. Ikhsan; et al. (Medicine (Baltimore), 2022)
This study aims to assess the prevalence, clinical, and ultrasonography (US) in thyroid screening in healthy subjects with general symptoms of thyroid abnormality in low iodine intake in Bajulmati primary care center, East Java Indonesia. We retrospectively reviewed US thyroid examination of 74 subjects with symptoms of mass in the neck, shaky, sleep difficulties, over sweating, and chronic fatigue on September 15th, 2021. Following the WHO guidelines, subjects also underwent physical examination in which the result were classified into 3 categories, that is, no palpable nor visible goiter, palpable but no visible goiter, as well as palpable and visible goiter. We evaluate US thyroid characteristics following Korean Society of Thyroid Radiology guidelines. Image analysis was reviewed by 4 general radiologists with 2 to 13 years’ experience. Categorical variables were compared using chi-squared or Fisher exact tests. Correlation between variables was measured with gamma statistics. Statistical analyses were conducted using IBM SPSS Statistics 23.0. A P-value < .05 was considered to indicate statistical significance. Of the 74 subjects, 32 (43.2%) show abnormalities. Statistical analysis showed no significant differences in the result of thyroid US in subjects with complaint fatigue (P = .464), insomnia (P = .777), over sweating (P = .158), and tremor (P = .778), but there were significant differences with the complaint of mass in the neck (P = .008). Furthermore, there was also a strong correlation between goiter palpation and US thyroid result (R = 0.773, P = .00). We conclude there were significant differences in US result of patients with and without complaint of mass in the neck. We also found a strong correlation between goiter palpation and US examination. Clinical findings, laboratory examination, cytology and molecular markers, patients’ age, nodules size, and ultrasound features should be considered for the treatment planning.